Pengaruh Kebijakan Dividen, Environmental Social Governance (ESG) dan Intellectual Capital terhadap Nilai Perusahaan - Sari, Nur Mila; Sutandijo, Sutandijo (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
The research aims to examine the relationship between dividend policy, ESG, and intellectual capital, as well as their impact on company value, and to provide empirical evidence to support these claims. Investors benefit most from the research results because their investment decisions can be strengthened by the data provided. For the 2020–2023 period, the research population included all companies listed on the IDX and included in the IDX ESG Leaders index. The research sample consisted of thirteen companies, selected using a purposive sampling technique. This research used a quantitative approach and utilized secondary data. Multiple linear regression analysis was applied to process the data. The results indicate that dividend policy, ESG, and intellectual capital simultaneously play a significant role in determining company value. However, when analyzed partially, ESG does not affect company value, in contrast to dividend policy and intellectual capital, which show a positive influence. This finding indicates that dividend policy and intellectual capital are important factors that deserve investor attention. Furthermore, the research results indicate that in the Indonesian context, dividend policy is highly valued because it can drive increased stock valuations; in other words, shareholders value companies more highly when dividends are distributed. Intellectual capital is also crucial in increasing company value. Meanwhile, in the Indonesian market, ESG issues are still not considered a major factor in determining stock prices.